Shared decision-making implementation status among dermatologists engaging in medical esthetics: a cross-sectional study in China - Li, Shiyuan; Fan, Jing; Qiang, Yan; Duan, Zhen; Wang, Ruiping (Frontiers in Medicine, 2024)
Objective: Shared decision making (SDM) is a collaborative process in which patients and healthcare providers jointly make a medical decision. This cross-sectional study aims to identify the implementation status of shared decision-making among dermatologists engaging in medical aesthetics in China and to identify factors associated with the good practice of SDM among them.From January to June 2023, A total of 1287 dermatologists engaging in medical aesthetic in China were recruited and completed the online interviews about their implementation of SDM based on the Shared Decision-Making Questionnaire for doctors (SDM-Q-Doc). Logistic regression was used to calculate the odds ratio (OR) and 95% confidence interval (CI) to explore factors associated with the higher SDM score achievement among dermatologists with medical aesthetic practice.The median value of the total SDM score was 39, and 48% (621/1278) of dermatologists with medical aesthetic practice achieved at least 40 out of 45 scores. Logistic regression indicated that dermatologists aged 40-49, or aged ≥50 and engaging in medical aesthetic practice for ≥5 years were more likely to have a higher proportion of achieving at least 40 out of 45 scores compared with dermatologists aged <30 and with less than 5 years of medical aesthetic practice, the OR was respectively 1.82 (95% CI: 1.13-3.12) , 1.94 (95% CI: 1.13-3.61) and 1.76 (95% CI: 1.34-2.31).The SDM implementation level among Chinese dermatologists engaging in medical aesthetics is high, especially for those with older age and more years of practice. So it is highly recommended to promote and enhance SDM practice among younger dermatologists engaging in medical aesthetics with less working experience.